Necessary but Not Sufficient: The Continuing Inequality between Men and Women in Educational Leadership, Findings from the American Association of School Administrators Mid-Decade Survey - Robinson, Kerry; Shakeshaft, Charol; Grogan, Margaret; Newcomb, Whitney Sherman (Frontiers in Education, 2017)
The gender of school leaders makes a difference in career paths, personal life, and characteristics of workplace. There is additional evidence that men and women are appointed or elected to lead different kinds of educational jurisdictions. Even if those differences did not exist, equitable access to leadership positions for people of different backgrounds would make this an important issue. This article reports gender-related findings from the American Association of School Administrators (AASA) 2015 Mid-Decade Survey. Findings confirm many of the trends in research on the superintendency over the past fifteen years. The profiles of women superintendents are becoming more like their male counterparts. Both men and women appear to be less mobile than in the past. Men and women are spending about the same time as teachers before becoming superintendents, women and men appear to experience stress similarly, and women are receiving mentoring much more than in the past. There are few data to support the beliefs that women superintendents, more than men are limited by family circumstance although this survey sheds no light on perspectives of women aspirants. This survey also confirms that there are a variety of paths to the position providing opportunities for women who have not necessarily had the typical teacher/principal/central office administrator trajectory. Nevertheless, significant differences still exist. Most important is that men are still four times more likely than women to serve in the most powerful position in education and both women and men of color are still grossly underrepresented.